Digital financial inclusion, population structure, and consumption upgrades: Evidence from China. - Qianwen Liu; Jianjie Zheng; Shihui Luo (PLoS ONE)
This study empirically tests the role of population structure in the process of digital financial inclusion empowering the upgrading of consumption structure by taking 248 prefecture-level cities between 2013 and 2019 as the research objects. The results of this study are as follows. First, digital financial inclusion will expand the scale of consumption. Second, digital financial inclusion can promote the upgrading of consumption structure. Third, population structure will regulate the promotional effect of digital financial inclusion on the upgrading of consumption structure. Specifically, child dependency ratio has a positive moderating effect on digital financial inclusion-driven the upgrading of consumption structure. Moreover, sex ratio has a positive moderating effect on digital financial inclusion-driven the upgrading of consumption structure. Therefore, it is suggested that vigorously promote and develop digital financial inclusion, implement and improve the three-child policy, and expand the elderly consumer industry to better promote consumption upgrading.